Birds in New York State Have Altered Their Migration Timing and Are Experiencing Different Thermal Regimes While Breeding or on Stopover from 2010 to 2015. (19th September 2017) - Pudalov, Natalie; Ziatek, Sydney; Jimenez, Ana Gabriela
Abstract : Migration represents a significant physiological challenge for birds, and increasing ambient temperatures due to global climate change may add to birds' physiological burden during migration. We analyzed migration timing in a central New York county and two counties in the Adirondack region by using data from the citizen science network, eBird, and correlating it with historical temperature data. Species of birds sighted in Central NY (N = 195 ) and the Adirondack region (N = 199 ) were categorized into year-round residents and one- and two-stopover groupings based on eBird observations. Using linear regressions, we looked at various relationships between temperature and variables relating to birds' migration across 2010–2015. Of the total 195 species used within this data in Central NY, 35 species showed some alteration in their migration timing or in the temperature regime they experienced while breeding or on migration stopover. In the Adirondack region, of the total 199 species used within this dataset, 43 species showed some alteration in their migration timing or experienced significantly colder or warmer temperatures while breeding or on migration stopover during 2010–2015. Additionally, many of the bird species affected by temperature changes in the state of New York and those that altered migration timing tended to be long-distance migrants.